Hydrothermal preparation of high saturation magnetization and coercivity cobalt ferrite nanocrystals without subsequent calcination - Huang, N.M.; Goh, S.C.; Chia, C.H.; Zakaria, S.; Yusoff, M.; Haw, C.Y.; Ahmadi, S.H; Lim, H.N. (Elsevier, 2010)
In this work, CoFe 2O 4 nanocrystals with high saturation magnetization (M s) and high coercivity (H c) have been fabricated via a simple hydrothermal method and without subsequent calcination. The resulting CoFe 2O 4 nanocrystals are characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, energy-dispersive X-ray spectrometry, differential scanning calorimetry and vibrating sample magnetometry. The results indicate that CoFe 2O 4 nanocrystals are single crystal and the average crystallite size is increasing with the hydrothermal temperature. The electron micrographs show that the nanocrystals are well-dispersed and possess uniform size. The shape of CoFe 2O 4 nanocrystals is transformed from spherical into rod by increasing the hydrothermal temperature. The nanocrystals show relatively high M s of 74.8 emu g -1 and H c of 2216 Oe, as compared to previous reported results. The obtained results reveal the applicability of this method for efficiently producing well crystallized and relatively high magnetic properties CoFe 2O 4 nanocrystals as compared to other methods. More importantly, it does not require further calcination processes. Â© 2009 Elsevier B.V. All rights reserved.